2008
DOI: 10.1126/science.1154986
|View full text |Cite
|
Sign up to set email alerts
|

An Agonist of Toll-Like Receptor 5 Has Radioprotective Activity in Mouse and Primate Models

Abstract: The toxicity of ionizing radiation is associated with massive apoptosis in radiosensitive organs. Here, we investigate whether a drug that activates a signaling mechanism used by tumor cells to suppress apoptosis can protect healthy cells from the harmful effects of radiation. We studied CBLB502, a polypeptide drug derived from Salmonella flagellin that binds to Toll-like receptor 5 (TLR5) and activates nuclear factor-kappaB signaling. A single injection of CBLB502 before lethal total-body irradiation protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
667
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(686 citation statements)
references
References 33 publications
15
667
1
3
Order By: Relevance
“…Recent study has shown that the activation of TLR5 by CBLB502 possesses radioprotective activity in mouse and primate models (Burdelya et al, 2008). More importantly, CBLB502 has no radioprotective effect on the tumors when it is administrated to tumor-bearing mouse treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has shown that the activation of TLR5 by CBLB502 possesses radioprotective activity in mouse and primate models (Burdelya et al, 2008). More importantly, CBLB502 has no radioprotective effect on the tumors when it is administrated to tumor-bearing mouse treated with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…CBLB502, a kind of polypeptide drug derived from Salmonella flagellin, can bind to TLR5 specifically and activate NF-kB signaling. Furthermore, it has been reported that CBLB502 has radioprotective activity in mouse and primate models (Burdelya et al, 2008).…”
Section: Toll-like Receptor 5 Agonist Inhibition Of Growth Of A549 Lumentioning
confidence: 99%
“…Interestingly, radiation protection of zebrafish embryos by NF-κB inhibitors extended to the gastrointestinal system whereas previous work using genetically modified mice 42 and the TLR5 ligand flagellin 43 has implicated NF-κB activation in radiation protection of gastrointestinal stem cells. The reason(s) for this difference are unclear at this point.…”
Section: B a E D C Fmentioning
confidence: 97%
“…This was done in consideration of several prior reports suggesting that NF-κB activation protects the gastrointestinal tract of higher vertebrates against acute radiation damage. 42,43 Radiation protection of the gastrointestinal system was determined in several ways. First, we assayed overall gastrointestinal function by scoring "long-term" survival of fish irradiated in the presence and absence of EP or CDDO-TFEA (up to 15 dpf).…”
Section: Organ-specific Radiation Protection By Cddo-tfea and Epmentioning
confidence: 99%
“…10 Interestingly, the microbiota seems to play a protective role in various experimental injury models including dextran sodium sulfate and radiation. [11][12][13] In contrast, global deletion of myeloid differentiation primary response gene (Myd88), an adaptor protein in innate immune signaling, protects mice from I/R-induced injury. 14 Moreover, in a model of necrotizing enterocolitis in newborn mice, TLR/MyD88-mediated intestinal injury seems to be controlled by nucleotide-binding oligomerization domain-2 signaling.…”
mentioning
confidence: 99%